Student Search: The Study of Ethics Educational Leadership Management - Suriyadi, Suriyadi; Sibuea, Bismar; Suardi, Suardi; Siahaan, Amiruddin; Nasution, Inom (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
Student Search is often interpreted as